The sFlt-1/PlGF ratio associates with prolongation and adverse outcome of pregnancy in women with (suspected) preeclampsia: analysis of a high-risk cohort. (April 2016) - Saleh, Langeza; Verdonk, Koen; Jan Danser, A.H.; Steegers, Eric A.P.; Russcher, Henk; van den Meiracker, Anton H.; Visser, Willy
Abstract: Objective: To evaluate the additive value of the sFlt-1/PlGF ratio for diagnosing preeclampsia (PE) and predicting prolongation of pregnancy and adverse outcome in a cohort of women with PE or at high risk of PE. Study design: Patients with suspected or confirmed clinical PE were recruited. At time of inclusion blood for measurement of sFlt-1and PlGF was taken. Values were determined after delivery. A cut-off ratio of ≥85 was defined as a positive test. Results: A total of 107 patients were included. Of the patients, 62 (58%) met the clinical criteria of PE at time of blood sampling. In 10% of these patients ( n = 6) the ratio was <85 (false negative), whereas in 7% ( n = 3) of patients without clinical PE the ratio was ≥85 (false positive), resulting in positive and negative predictive values of 95% and 88% respectively. One patient with false positive ratio developed superimposed PE and 2 developed gestational hypertension, and adverse outcome occurred in all three. An adverse pregnancy outcome was only encountered in 1 of the 6 patients with a false negative ratio. Using a binary regression model with adjustment for gestational age <34 weeks, the adverse outcome risk was 11 times increased on the basis of clinical PE, and 30 times on the basis of an elevated ratio ( P = 0.036). Conclusion: The additive value of an increased ratio for diagnosing PE is limited since most patients with clinical PE also have a positive ratio. However, an elevated ratio is superior to the clinical diagnosis of PE for predicting an adverse pregnancy outcome. Furthermore, irrespective of clinical PE, a low ratio is inversely correlated with prolongation of pregnancy.